A randomized, prospective, comparative trial of a variable‐angle versus fixed‐angle endoscope for exploratory thoracoscopy in canine cadavers. (23rd June 2020) - Diamond, Danielle M.; Scharf, Valery F.; Chiu, King Wa; Hash, Jonathan A.; Mathews, Kyle G.
Abstract: Objective: To compare the efficacy of a variable‐angle endoscope (VAE) for canine thoracoscopic exploration to a traditional fixed‐angle endoscope (FAE). Study design: Randomized, prospective, comparative study. Sample population: Five fresh canine cadavers. Methods: Twelve predetermined anatomical locations were labeled after median sternotomy in each cadaveric thorax. Two board‐certified veterinary surgeons performed thoracoscopic evaluation of each thorax using a fixed‐angle (30°) and a variable‐angle (0°‐120°) endoscope with and without lungs mechanically ventilated. The order of surgeon, lung ventilation, and endoscope were determined using a randomized block design. Time to visualize each anatomical location was compared for surgeon, endoscope, and lung ventilation status. Primary outcome measures were time to individual anatomical location, total simulated thoracoscopic exploration time, and ability to identify anatomical location within the designated time period. Results: Lung ventilation (difference = 184 seconds, P  = .015, 95% CI = 45‐342 seconds) and endoscope type (difference = 112 seconds, P  = .029; 95% CI = 10‐213 seconds) had an effect on the cumulative time for complete thoracoscopic exploration. The VAE shortened the time to identify three of the 12 anatomical locations when controlling for the effects of lung ventilation. Use of the VAE did not improve time to identification for any locations compared to the FAE when lungs were not ventilated. The VAE facilitated significantly shorter cumulative thoracoscopic exploration time compared with the FAE. Failure to identify predetermined locations was more common with the FAE than with the VAE. Conclusion: Use of a rigid VAE decreased cumulative thoracoscopic exploration time and provided an alternative to one‐lung ventilation for circumventing the visual impediments of lung ventilation. Clinical significance: This cadaveric study provides evidence that one‐lung ventilation and use of a VAE may improve surgeon efficiency during exploratory thoracoscopy.